Analysis of Semiotics and Gender Equality Message in the ABC‘s Soy Sauce Advertisement #SuamiIstriMasak Edition - Nalisaputri, Juliarni (Jurnal Penelitian Mahasiswa Indonesia, 2023)
The ABC soy sauce advertisement #SuamiIstriMasak edition is one of ABC’s soy sauce advertisements that resulted from a series of gender equality campaigns. ABC’s soy sauce continues its commitment to gender equality, especially regarding the division of responsibilities in the kitchen, which means that not only the wife cooks in the kitchen but the men can also cook and help in the kitchen. This advertisement conveys a message of gender equality, which is conveyed visually in the advertisements. This study aims to determine how the visual message of gender equality can be conveyed with the meaning of denotation, connotation, and myth in the ABC’s soy sauce advertisement of the #SuamiIstriMasak edition using Roland Barthes’ semiotic analysis. This research used Roland Barthes’ approach with the descriptive qualitative research method. The stages were making background, problems, purposes, research methods, collecting data, analyzing, discussing, and conclusions. The result of this study is an analysis of selected scenes from ABC’s soy sauce advertisement of the #SuamiIstriMasak edition which most support the existence of gender equality message and then analyzed with the meaning of Roland Barthes’ semiotics, namely denotative, connotative, and myth.